The Impact of Price Perception, Religious Commitment, and Halal Certification on Online Buying Behavior of Make Over Halal Cosmetics - Purba, Na'imi Salwa; Harahap, Isnaini; B Syarbani Tanjung, Ahmad Muhaisin (Universitas Ibn Khladun Bogor, 2025)
This research seeks to examine how price perception, religiosity, and halal labeling affect the online purchase decisions of Make Over halal cosmetic products among university students in Medan. The study employed a quantitative research design, utilizing a survey technique with a structured The research utilized a questionnaire for data collection, followed by analysis through Structural Equation Modeling (SEM). The findings indicated that price perception, religiosity, and halal labeling, as the three independent variables, had a significant impact on purchasing decisions. Among the variables, the halal label exerted the strongest influence, followed by price perception and religiosity. The coefficient of determination (R²) value of 0.883 indicates that the model is able to explain 88.3% of the variation in purchasing decisions. These findings emphasize the importance of halal labels as a guarantee of trust for Muslim consumers, as well as the role of competitive prices and levels of religiosity in driving online purchasing decisions of halal cosmetics. The implications of this study provide recommendations for manufacturers and marketers to improve marketing strategies that emphasize halal aspects, affordable prices, and religious values to strengthen Muslim consumer loyalty in the online halal cosmetics market.